2016
DOI: 10.1097/hp.0000000000000491
|View full text |Cite
|
Sign up to set email alerts
|

Aerial Mobile Radiation Survey Following Detonation of a Radiological Dispersal Device

Abstract: A series of experiments was conducted in 2012 at the Defence Research and Development Canada's Suffield Research Centre in Alberta, Canada, during which three radiological dispersal devices were detonated. The detonations released radioactive (140)La into the air, which was then carried by winds and detectable over distances of up to 2 km. The Nuclear Emergency Response group of Natural Resources Canada conducted airborne radiometric surveys shortly following the explosions to map the pattern of radioactivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 15 publications
1
21
0
Order By: Relevance
“…These plots are most accurate when using a technique like in situ gamma measurements that intrinsically average over a wide area, as witnessed by the good agreement between the RadEye PRD array measurements and the airborne measurements reported by Sinclair et al (2016). For these trials, measurements showed that 15-30% of the original source was deposited within 450 m from ground zero.…”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations
“…These plots are most accurate when using a technique like in situ gamma measurements that intrinsically average over a wide area, as witnessed by the good agreement between the RadEye PRD array measurements and the airborne measurements reported by Sinclair et al (2016). For these trials, measurements showed that 15-30% of the original source was deposited within 450 m from ground zero.…”
Section: Resultsmentioning
confidence: 62%
“…Again, the data for shot 3 are suspect due to the path of the plume. Another comparison between these deposition plots and those reported by Sinclair et al (2016) from helicopter survey data. Their helicopter survey cumulative deposition plots show deposition (up to~450 m from ground zero) consistent with a deposition velocity, v d = 35 mm s −1 for shot 1 and v d = 20 mm s −1 for shot 2.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Measurements of the deposition are presented in three papers. Erhardt et al (2016) present deposition measurements taken using handheld and fixed-point, in situ, beta and gamma detectors, Sinclair et al (2016) present aerial survey measurements of the deposition, and Berg et al (2016) present laboratory analysis of measurements using passive deposition filters. Comparison of dispersion model results to the FSRDD Field Trial measurements and analysis of model performance are presented in four papers.…”
Section: Full-scale Radiological Dispersal Device Field Trialsmentioning
confidence: 99%